A molecular phylogeny of the cosmopolitan hyperdiverse genus Hydraena Kugelann (Coleoptera, Hydraenidae). (22nd October 2012) - TRIZZINO, MARCO; JÄCH, MANFRED A.; AUDISIO, PAOLO; ALONSO, ROCIO; RIBERA, IGNACIO
Abstract : With almost 900 described species, Hydraena Kugelann (Hydraenidae) is one of the largest genera among Coleoptera. The subgeneric classification of Hydraena has been controversial, with 11 subgeneric names having so far been attributed to it. Some of these, Haenydra Rey and Spanglerina Perkins, have been treated as valid genera, as subgenera or as species groups. The most recent complete treatment of the genus, based on a cladistic analysis of morphological characters, recognized two major lineages, and only these were classified as subgenera: Hydraenopsis (mainly Gondwanan distribution), and Hydraena s.str. (mainly Laurasian). Here, we reconstruct the phylogeny of Hydraena using 212 species plus several outgroups and approximately 4 kb of sequence data from two nuclear ( SSU and LSU ) and four mitochondrial genes ( cox1, rrnL, trnL and nad1 ). Data were aligned with two different strategies of multiple alignment (implemented inmafft andprank ), and the phylogenies reconstructed using maximum likelihood and Bayesian methods. We estimated approximate ages of the main nodes using a relaxed molecular clock with Bayesian methods, and an a priori evolutionary rate of 0.01 substitutions/site/million years (Ma) plus a calibration point based on a biogeographical split. We found strong support for the monophyly of Hydraena and many of the clades recognized with morphological data. The following clades are considered as subgenera: Phothydraena Kuwert, Spanglerina Perkins, Holcohydraena Kuwert, Hydraenopsis Janssens and Hydraena s.str. The placement of three species groups, two Neotropical ( H. multispina group, H. paeminosa group) and one South African/Madagascan ( H. monikae group), is uncertain, and they are considered incertae sedis within Hydraena . The origin of the genus was estimated to be in the Lower Eocene, with many species complexes diversifying in the Pleistocene. Dispersal events seem to have played a key role in order to determine the current distribution of the species groups in the southern hemisphere (mainly in Hydraenopsis ).